Validation of a photophobia symptom impact scale. (October 2019) - Cortez, Melissa M; Digre, Kathleen; Uddin, Durin; Hung, Man; Blitzer, Andrea; Bounsanga, Jerry; Voss, Maren W; Katz, Bradley J
Background: Routine assessment of photophobia in the clinical setting may underestimate the presence and severity of this condition. We aimed to develop and validate a questionnaire to improve evaluation of the impact of photophobia on activities of daily living, and to determine the relationship of this questionnaire to psychophysical assessment of light sensitivity thresholds. Methods: We developed the 17-item Utah Photophobia Symptom Impact Scale (UPSIS-17) and compared its psychometric properties to the 8-item Korean Photophobia Questionnaire (KUMC-8). Ninety five subjects with or without light sensitivity completed both questionnaires; 72 also completed laboratory-based assessment of light sensitivity thresholds. We used Rasch analysis to evaluate instrument targeting, including internal consistency and reliability. Correlation analysis was used to assess the relationship between questionnaire scores and light sensitivity thresholds. Results: We observed correlation between UPSIS-17 and KUMC-8, r = 0.72 ( p  < 0.0001). Higher UPSIS-17 scores correlated with light sensitivity thresholds, r = −0.42 ( p  < 0.0001), whereas KUMC-8 scores did not significantly correlate with light sensitivity thresholds, r = −0.21 ( p  = 0.072). UPSIS-17 showed better instrument targeting than KUMC-8 on Rasch analysis. Person-item maps allowed for identification of questions that could be removed without affecting questionnaire validity measures. Conclusion: This study resulted in a shortened, 12-item questionnaire. The UPSIS-12 retained significant correlation with both the KUMC-8 and light sensitivity thresholds, yielding a simpler tool for symptom assessment, while retaining validity. This expanded tool may be useful in clinical, as well as research settings, for collection of data about disability due to photophobia.